Peranan Orang Tua Memotivasi Siswa Kelas V SDN 57 Air Dingin Koto Tangah Tahun 2022/2023 dalam Melaksanakan Shalat Wajib - Khatimah, Siti Husnul; Ikhlas, Al (Lembaga Yasin AlSys, 2023)
This research aims to describe the role of parents in activate student's internal motivation to do obligatory prayers in fifth grade students of SD Negeri 57 Air Dingin Koto Tangah, and describe about how the role of parents is so that children have eksternal motivation towards the habit to do prayer for fifth grade students SD Negeri 57 Air Dingin Koto Tangah. This research uses qualitative methods, namely research that describes and analyzes an event, phenomenon, social activity, and thoughts that describe to draw conclusions. The research's type is case study. That is where a researcher conducts an in-depth exploration of programs, events, processes, activities, against one or more people. The research results based on observations, questionnaires, interviews, and documentation show that the role of parents has a very influential impact on guiding their children to become obedient human beings in carrying out their duty as a Muslim, being grateful, and thanking to Allah Ta'ala.